The value of non-invasive computed tomography coronary angiography in imaging patients with coronary artery bypass grafts. Issue 3 (August 2020) - Krysztofiak, T; Ahmad, F; Adams, J; Stobo, DB; Good, R; Byrne, J
Introduction: Invasive coronary angiography (ICA) is associated with higher complication rates in patients following coronary artery bypass surgery (CABG). CT coronary angiography (CTCA) has emerged as an attractive alternative. We assessed the impact of CTCA on subsequent ICA. Methods: We identified 213 CABG patients undergoing CTCA between 2015 and 2018. In 151 the indication was suspected recurrence of angina. We then identified patients undergoing ICA within 1 year of CTCA. Results: CTCA obviated the need for ICA in 115 cases (76%). CTCA was better at identifying targets for percutaneous coronary intervention (PCI) to saphenous vein grafts (SVG's) than to native vessels (89% vs 47%). 7 out of 10 lesions of "probable" significance by CTCA proved flow-limiting, and 4 out of 13 "indeterminate" lesions. CTCA concordance was 97% for left internal mammary (LIMA) grafts. Conclusion: CTCA directed management in a majority of patients without ICA. It identified a cohort of patients likely to be candidates for SVG PCI, but was less effective in identifying PCI targets in the native vessels. CTCA renders invasive LIMA cannulation redundant unless a target lesion is suspected.